The taxonomic status of Ruschia stricta var. turgida and R. promontorii and a new name for R. vaginata (Ruschieae, Aizoaceae) - Klak, Cornelia; Schmiedel, Ute; Bruyns, Peter V. (Phytotaxa, 2020)
The taxonomic position of two succulent members of the Ruschieae (Aizoaceae), Ruschia stricta var. turgida and R. promontorii, that are currently placed in Amphibolia, is revised on account of new morphological information. Ruschia stricta var. turgida, endemic to the Knersvlakte (Western Cape, South Africa), is characterized by 6-locular fruits, the lack of closing bodies and the lack of filamentous staminodes. Amphibolia has 5-locular fruits with closing bodies and flowers with filamentous staminodes. Consequently, R. stricta var. turgida cannot belong to Amphibolia. On account of differences in the fruits and inflorescences, we recognize R. stricta var. turgida as a distinct species. We show that R. promontorii is different from Amphibolia laevis, of which it has been considered to be a synonym. In particular, these two differ by their ecological preferences and by certain morphological features. In addition, a new name, Ruschia vaginella, is published for the illegitimate Ruschia vaginata.